PERTIMBANGAN HAKIM TERHADAP PENETAPAN DISPENSASI PERKAWINAN DI PENGADILAN AGAMA KOTA SUKABUMI TAHUN 2019 - Iswandi, Saida Nurfadila (LPPM STAI DARUSSALAM LAMPUNG, 2019)
This article aims to describe the Judge's Consideration of the Determination of Marriage Dispensation at the Sukabumi City Religious Court in 2019. One of the requirements for marriage is the minimum age limit in accordance with Article 7 paragraph (1) of Law No. 16 of 2019 which states that